Transitioning from recruit to officer: An investigation of how stress appraisal and coping influence work engagement - Rodrigues, Susana (2019)
This study investigated stress, coping, and work engagement among Portuguese police officers while undergoing academy training and then 1 year later, when on duty. It was hypothesized that stress appraisal and coping preferences predicted engagement. Additionally, in order to test a full cross‐lagged prediction model, it was hypothesized that stress, coping, and engagement in recruits predicted these variables later when working as police officers. Structural equation modeling was used to test the research hypotheses. Results suggest that coping and stress appraisals do not seem to be strong predictors of work engagement among recruits and police officers on duty. With the exception of self‐blame, that seems to be a strong predictor of work engagement among police officers on duty. These results highlight the need to investigate other potential variables such as working conditions that may better explain work engagement. Considering the positive influence of engagement on health, wellbeing, and performance of police recruits and officers future applied and theoretical implications are discussed.